Monosomy X rescue explains discordant NIPT results and leads to uniparental isodisomy. (24th September 2018) - Rudd, M. Katharine; Schleede, Justin B.; Williams, Sabrina R.; Lee, Kristy; Laffin, Jennifer; Pasion, Romela; Papenhausen, Peter R.
Abstract: Noninvasive prenatal testing accurately detects trisomy for chromosomes 13, 21, and 18, but has a significantly lower positive predictive value for monosomy X. Discordant monosomy X results are often assumed to be due to maternal mosaicism, usually without maternal follow‐up. We describe a case of monosomy X‐positive noninvasive prenatal testing that was discordant with the 46, XX results from amniocentesis and postnatal testing. This monosomy X pregnancy doubled the single X chromosome, leading to 45, X/46, XX mosaicism in the placenta and uniparental isodisomy X in the amniotic fluid. Thus, at least some discordant monosomy X results are due to true mosaicism in the pregnancy, which has important implications for clinical outcome and patient counseling. Abstract : What's already known about this topic? Most pregnancies that screen positive for monosomy X by noninvasive prenatal testing (NIPT) do not detect a 45, X karyotype in follow‐up invasive testing. Indeed, the positive predictive value (PPV) for monosomy X is 23% to 26%, much lower than PPV for other common aneuploidies. What does this study add? In our study, discordant testing results for monosomy X are explained by monosomy rescue during the pregnancy. Although monosomy rescue to disomy can ameliorate some of the features of Turner syndrome, the 2 X chromosomes will be identical and derived from 1 parent, known as uniparental isodisomy.